Newton/Julia Fractal (734)
![イメージ 1]()
![イメージ 2]()
![イメージ 3]()
![イメージ 4]()
![イメージ 5]()
![イメージ 6]()
![イメージ 7]()
![イメージ 8]()
![イメージ 9]()
![イメージ 10]()
![イメージ 11]()
![イメージ 12]()
![イメージ 14]()
f(z) = z - (3*z*(z+1/2)^3-2*(z/3+1)/2.8)/(12/5*z^3+27*?(?(z^2))+18*z+1)
Univers Mandala
Sonate K886 Spirale de Mandala
Newton/Julia Fractal (735)
f(z) = z - (3*z*(z+1/2)^3-2*(z/3+1)/2.8)/(12/5*z^3+27*?(?(z^2))+18*z+1)
Sonate K888
Newton/Julia Fractal (736)
f(z) = z - (3*z*(z+1/2)^3-2*(z/3+1)/2.8)/(12/5*z^3+27*?(?(z^2))+18*z+1)
Sonate K890
Newton/Julia Fractal (737)
f(z) = z - (3*z*(z+1/2)^3-2*(z/3+1)/2.8)/(12/5*z^3+27*?(?(z^2))+18*z+1)
Sonate K892
Newton/Julia Fractal (738)
f(z) = z - (3*z*(z+1/2)^3-2*(z/3+1)/2.8)/(12/5*z^3+27*?(?(z^2))+18*z+1)
Sonate K894
Newton/Julia Fractal (739)
f(z) = z - (3*z*(z+1/2)^3-2*(z/3+1)/2.8)/(12/5*z^3+27*?(?(z)^2)+18*z+1)
Newton/Julia Fractal (740)
f(z) = z - (3*z*(z+1/2)^3-2*(z/3+1)/2.8)/(12/5*z^3+27*?(?(z)^2)+18*?(z)+1)
Newton/Julia Fractal (741)
![イメージ 13]()
f(z) = z - (3*z*(z+1/2)^3-2*(z/3+1)/2.8)/(12/5*?(z^3)+27*z^2+18*z+1)
Sonate K898 Spirale de Coq Noir